Effects of wheat tempering and stone rotational speed on particle size, dough rheology and bread characteristics for a stone-milled weak flour. (January 2020) - Cappelli, Alessio; Guerrini, Lorenzo; Parenti, Alessandro; Palladino, Gennaro; Cini, Enrico
Abstract: The poor technological performance of weak wheat flours means that they are usually considered difficult to be transformed into satisfactory bread. During milling, there are several settings that can affect flour characteristics. In this study, we tested two operative parameters that have the potential to affect flour quality – stone rotational speed and wheat tempering. Tempering moistures were set at 11%, 13%, 15%, and 17%, while stone rotational speeds were set at 173, 260, and 346 rpm. Both factors were found to affect operative milling parameters, notably flour yield, process productivity and specific energy consumption. Grain moisture had a significant effect on both dough rheology and bread characteristics (dough stability, tenacity, and extensibility). Dough stability was maximum at 13% moisture. Dough tenacity decreased as moisture increased, while extensibility increased as moisture increased. Bread specific volume and crumb specific volume were improved at 13% and 15% moisture. In conclusion, wheat tempering can be used to improve the potential of a weak flour and bread characteristics, while stone rotational speed affects operative parameters and white flour yield. Graphical abstract: Image 1 Highlights: The effect of milling speed and wheat tempering was evaluated. Differences in milling efficiency, dough rheology and bread quality were assessed. Milling speed affected flour yield, productivity and specific energy consumption. Wheat tempering had a significant effect on both dough rheology and bread quality. 13% moisture is the best compromise between milling and breadmaking performance.